Andrzej Wróblewski - exhibiting - Banai, Noit; Bieńczyk, Marek 1956-; Boniecki, Adam 1934-; Ciechańska, Marzenna; Fowkes, Maja; Fowkes, Reuben 1971-; Gauger, Soren A. 1975-; Gillen, Eckhart 1947-; Gołubiew, Zofia 1942-2022; Hatherley, Owen 1981-; Holert, Tom 1962-; Jarecka, Dorota 1966-; et al. (Hatje Cantz, 2024)
Throughout his life, Polish painter Andrzej Wróblewski (1927-57) moved on the fringes of society; contemporaries described him as a "painter of a tragic generation." This publication explores the reception of his work - somber portraits and images of city life rendered in a cool, muted palette
Keywords: Wróblewski, Andrzej -- 1927-1957; Malerei; Ausstellung; Wróblewski, Andrzej / (1927-1957); Malarstwo polskie; Rysunek polski; Wystawy sztuki; Europa; Polska; 1901-2000; 1945-1989; 1989-2000; 2001-; Praca zbiorowa; Publikacja bogato ilustrowana